The Impact of Domestic Debt on Private Investment in The Gambia: An ARDL Approach - Ebrima Gomez; Bilge Kağan Ozdemir (Ekonomi, Politika & Finans Araştırmaları Dergisi, 2020)
This study aims to analyse the impact of domestic debt on private investment in the Gambia by developing an investment model based on the neoclassical investment function and considered an annual time series data set from 1980 to 2013. To examine the nexus between our dependent variable, private investment and the explanatory variables, we used an Autoregressive Distributed Lag (ARDL) model. Based on the bounds test result, a long run relationship exists between our variables. Furthermore, domestic debt was found to have a negative effect on private investment in the short run but not in the long run. On the other hand, the real interest rates had a crowding-out effect on private investment in the long run but a positive effect in the short run. This study will be a guide for policymakers on formulating fiscal and monetary policies to curb the level of domestic borrowing to optimal or sustainable levels.